Manajemen Pengelolaan Taman Wisata Laut Labuhan, Sepulu (Studi Pada Pokdarwis Payung Kuning) - Ayu Silviana Arifin; Faidal Faidal (Management Department of Economics and Business Of Trunojoyo Madura University, 2022)
This study aims to determine the management of Taman Wisata Laut Labuhan, about the work culture, and interpersonal communication that occurs in members of the pokdarwis payung kuning and SMEs. The method used in this research is descriptive with an interpretative qualitative approach, while the data collection techniques used are interviews, observation, and documentation. The data analysis techniques using data reduction, data presentation and drawing conclusions. Then to test the validity of the data using source triangulation, triangulation techniques, and time triangulation.The results of the study indicate that the management of the Taman Wisata Laut has been running in accordance with mutually agreed rules. The Pokdarwis Payung Kuning as the manager has good planning for the development of tourist sites. The work culture of the Pokdarwis payung kuning is by prioritizing togetherness with mutual agreement and enthusiasm and unyielding in carrying out work in accordance with the positions and duties of each member. Coordination that runs smoothly with related institutions and agencies in the management of existing facilities and infrastructure, as well as intense interpersonal communication makes the management of this Taman Wisata Laut become responsive in solving problems that occur in the management of Taman Wisata Laut.